Characterization of corn starch edible films by the addition of chitosan as a vegetable oil packaging material - Wicakso, Doni Rahmat; Fortuna, Dwi; Hernadin, Ivan Aldino; Nuryoto, Nuryoto; Rumbino, Yusuf; Damayanti, Astrilia (Konversi, 2023)
Abstract - Vegetable oil packaging materials use a type of synthetic polymer that is harmful to the body and the environment. Edible film as an environmentally friendly packaging material can be a solution for vegetable oil packaging material. Edible films are made from natural ingredients such as starch and chitosan. The objective of this study is to determine the best conditions of addition of chitosan in making edible film in terms of its physio-chemicals and determine the best glycerol concentration in terms of its physical properties. The composition of raw materials in the form of corn starch is 5 grams and the composition of chitosan is (0,5%, 1% and 1,5% b/v). Glycerol concentrations vary in (4%, 5% and 6% v/v). the result of the analysis of the physical properties of the edible film through the analysis of the physical tensile strength test, namely the best composition on the addition of 1 gr chitosan as well as the elongation analysis at termination. Analysis of the solubility of the edible film at a concentration of 1 gr as well the analysis of water vapor permeability. Whereas the analysis of the best antioxidant capacity in the composition of chitosan is 1,5 gr. Keywords: corn starch, chitosan, edible film